Effect of Concomitant Drug Use on the Onset and Exacerbation of Diabetes Mellitus in Everolimus-Treated Cancer - Katsuhiro Ohyama; Hiroyuki Tanaka; Yusuke Hori (Frontiers Media S.A., 2022)
Purpose: Everolimus-induced diabetes mellitus (DM) outcomes include everolimus-resistant tumors and poor hyperglycemia outcomes, which lead to various other negative clinical outcomes. This study aimed to evaluate the effect of associations between concomitant drug treatment and time to DM event occurrence (onset or exacerbation) on the outcomes of everolimus-induced DM in patients with cancer. Methods: Data from the Japanese Adverse Drug Event Report database (JADER) were used, and patient drug use, time of DM event occurrence, and DM outcomes were determined from patient records. Associations between concomitant drug groups with everolimus and DM event occurrence were then evaluated for patients with both good and poor DM outcomes. Results: Top ten groups used concomitantly were drugs for the treatment of hypertension (HT), controlled DM, constipation, hypothyroidism, kidney disease, insomnia, hyperlipidemia, hyperuricemia, anemia, and gastritis. Among them, only HT, controlled DM, and hyperlipidemia were associated with DM event occurrence. These three drug groups were examined by the outcome of everolimus concomitant usage and revealed a significantly shorter time to DM event occurrence for patients with poor outcomes than for those with good outcomes (p = 0.015) among patients without a concomitant drug for DM. Each of these three drug groups was analyzed on patients who were concomitantly administered with one of each drug group with everolimus and revealed a significantly shorter time to DM event occurrence for patients with poor outcomes than for those with good outcomes in patients who received concomitant HT drugs (p = 0.006). Moreover, among the four HT drug categories, calcium channel blockers were significantly associated with poor outcomes (odds ratio, 2.18 [1.09-4.34], p = 0.028). Conclusion: To prevent everolimus-induced poor DM outcomes, early DM detection and treatment are necessary, and the effect of the concomitant drug should be considered before initiating everolimus treatment.